Ion versus pH sensitivity of ungated AlGaN/GaN heterostructure-based devices - Podolska, Anna; Kocan, M.; Garces Cabezas, A.; Wilson, T.; Umana-Membreno, G.; Nener, B.; Parish, G.; Keller, S.; Mishra, U. (American Institute of Physics, 2010)
We have investigated the pH and ion sensitivity of AlGaN/GaN heterostructure devices; these devices are sensitive to the ion concentration rather than to the pH of the solution. Sheet resistance as a function of pH for calibrated pH solutions and dilute NaOH, HCl, KOH, and NaCl showed an increase as a function of ionic concentration, regardless of whether the pH was acidic, basic, or neutral. An increase in resistance corresponds to accumulation of negative ions at the AlGaN surface, indicating device selectivity toward the negative ions. We attribute this to the formation of a double layer at the liquid/semiconductor interface.